High and low inferior mesenteric artery ligation in laparoscopic low anterior rectal resections: A retrospective study - Yu, Jun; Chen, Yi; Li, Tong; Sheng, Bo; Zhen, Zhuo; Liu, Chang; Zhang, Jianbo; Yan, Qian; Zhu, Peng (Frontiers in Surgery, 2023)
Backgrou: The high or low inferior mesenteric artery (IMA) ligation in rectal cancer remains a great debate. This study retrospectively discussed the outcomes of the perioperative period, defecation and urinary function and long-term prognosis in rectal cancer patients with high or low IMA ligation. Methods: This study enrolled 220 consecutive rectal cancer cases, including 134 with high IMA ligation and 86 with low ligation. A comparison between the two groups was made for anastomotic leakage, low anterior resection syndrome (LARS), international Prostate Symptom Score (IPSS), 5-year disease-free survival (DFS) and 5-year overall survival (OS). Results: Low-ligation group had a longer operative time, and larger intraoperative blood loss. No significant difference was noted in anastomotic leakage incidence. In multivariable analysis, the male gender and tumor located at the lower rectum were identified as risk factors for anastomotic leakage. No significant differences were observed between groups in their LARS and IPSS questionnaire responses. The high-ligation versus the low-ligation 5-year OS and DFS were 78.3% versus 82.4% and 72.4% versus 76.6%, respectively, which were not statistically different. Conclusion: The ligation level of the IMA had no significant effect on the anastomotic leakage incidence, defecation, urinary function, and long-term prognosis.